Induction Response in Patients of Classical Hodgkin Lymphoma of Pediatric Age Group as Asseseed by CT Scan Post Chemotherapy Induction - Awan, Haider Ali Awan; Ahmed, Waqas; Ahmed, Shakeel; Malik, Sumbal; Akhlaq, Bilal; Mehmood, Rehan (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the induction response to chemotherapy as adequate or inadequate using CT (computed tomography) scan texture analysis parameters in pediatric patients of classical Hodgkin lymphoma when compared with the gold standard PET findings. Study Design: Prospective longitudinal study Place and Duration of Study: Pediatrics department of Combined Military Hospital, Rawalpindi Pakistan, from Jan 2023 to Dec 2023. Methodology: After the histopathological diagnosis was confirmed, Positron emission tomography and Computed tomography scans were done in all patients before the start and the end of two cycles of chemotherapy and response to treatment was compared using imaging changes before and after the procedure. Primary variables measured were early response assessment (ERA) by adequate and inadequate response to chemotherapy assessed by Computed tomography scan findings compared to those of Positron emission tomography scan results. Sensitivity and specificity was also calculated for Computed tomography findings versus Positron ...... Results: Radiological lesion analysis by independent consultants for PET and CT scan for the tumors showed that patients showed adequate early response in 94(78.3%) cases in PET scan results versus 59(49.2%) cases on CT scan findings. Similarly inadequate response was labelled in 26(21.7%) cases when assessed by PET scan and 61(50.8%) when labeled after assessment of texture analysis of tumors on CT scan (p=0.034). The sensitivity of CT scan in detecting adequate and inadequate response .. .. Conclusion: We conclude that CT scan shows low sensitivity and specificity in detecting adequate and inadequate response to early stage chemotherapy in pediatric Hodgkin Lymphoma with ...